Agroforestry practices in leasehold forests in Tanahun, a Mid-hill district of Western Nepal - Shakya, R; Baral, SK; Basukala, R; Khanal, S (Banko Janakari, 2008)
(Author of this paper, S Khanal was omitted in error - added on 29-3-2010) Leasehold forestry in Nepal has sought to address both poverty alleviation and environmental conservation. The major agroforestry practices observed in the leasehold forests were silvopasture, hortisilviculture and Non Timber Forest Product (NTFP) cultivation. The most prominent problem to the users in adopting agroforestry practices was the lack of technical information. Some successful insights observed suggest that agroforestry has a notable potential to address dual objectives of poverty alleviation and conservation. The need to evolve sustainable mechanism for promoting agrofrorestry in degraded lands through the dissemination of useful traditional knowledge, innovative practices and improved technologies was identified. Key words: Leasehold forest; agroforestry; silvopasture; hortisilviculture; NTFP Banko Janakari Vol.16(2) 2006 pp.45-49